Mitochondrial cardiomyopathy and ventricular arrhythmias associated with biallelic variants in C1QBP. Issue 8 (18th May 2021) - Webster, Gregory; Reynolds, Meredith; Arva, Nicoleta C.; Dellefave‐Castillo, Lisa M.; McElligott, Hilary S.; Kofman, Amber; Laboski, Aleksandra; Magnetta, Defne; George, Alfred L.; McNally, Elizabeth M.; Puckelwartz, Megan J.
Abstract: Patients with biallelic mutations in the nuclear‐encoded mitochondrial gene C1QBP/p32 have been described with syndromic features and autosomal recessive cardiomyopathy. We describe the clinical course in two siblings who developed cardiomyopathy and ventricular fibrillation in infancy. We provide genomic analysis and clinical‐pathologic correlation. Both siblings had profound cardiac failure with ventricular arrhythmia. One child died suddenly. The second sibling survived resuscitation but required extracorporeal cardiopulmonary support and died shortly afterward. On cardiac autopsy, the left ventricle was hypertrophied in both children. Histological examination revealed prominent cardiomyocyte cytoplasmic clearing, and electron microscopy confirmed abnormal mitochondrial structure within cardiomyocytes. DNA sequencing revealed compound heterozygous variants in C1QBP (p.Thr40Asnfs*45 and p.Phe204Leu) in both children. Family segregation analysis demonstrated each variant was inherited from an unaffected, heterozygous parent. Inherited loss of C1QBP/p32 is associated with recessive cardiomyopathy, ventricular fibrillation, and sudden death in early life. Ultrastructural mitochondrial evaluation in the second child was similar to findings in engineered C1qbp ‐deficient mice. Rapid trio analysis can define rare biallelic variants in genes that may be implicated in sudden death and facilitate medical management and family planning. (184/200 ) .